Molecular engineering of 1, 3, 5-triaryl-2-pyrazoline fluorescent logic systems responsive to acidity and oxidisability and attachment to polymer beads. Issue 1 (8th December 2020) - Zerafa, Nicole; Cini, Miriam; Magri, David C.
Abstract : Designed fluorescent logic gates based on PET and ICT emulating NOT, off–on–off and INHIBIT logic functions are covalently attached to PEG–polystyrene polymer beads. Abstract : 1, 3, 5-Triaryl-2-pyrazolines were designed, synthesised and covalently immobilised onto submillimetre TentaGel® polystyrene beads (functionalised with amino-terminated polyethyleneglycol ligands) by peptide bond formation. The molecules are modularly designed based on photoinduced electron transfer (PET) according to electron-donor–spacer–fluorophore–receptor and receptor 1 –spacer–fluorophore–receptor formats with ferrocene and N, N -dimethylaniline as the electron donor and receptor1 . A reference fluorophore–receptor compound, associated with an internal charge transfer (ICT) mechanism, is included for comparison. A carboxylate moiety at the para -position of the 1-phenyl ring assists the molecules with aqueous solubility and serves as the site for covalent attachment to the polystyrene beads. The H +, Fe 3+ -driven INHIBIT, H + -driven off–on–off and H + -driven NOT logic systems are demonstrated in aqueous methanol and attached onto heterogeneous polymer submillimeter beads. The INHIBIT gate was tested with the stronger oxidant, ammonium persulfate, which resulted in a greater fluorescence quantum yield ( Φ f = 0.192). A double-tagged polymer bead integrating INHIBIT and off–on–off multi-valued logic was also prepared.